(untitled) (The Research of Medical Science Review, 2025)
The aim of this study was to ascertain the rate of occurrence of vaginal candidiasis in women visiting Timergara Teaching Hospital from 2024 August to 2024 December. That contained data on age, marital status, level of education, occupation, health history, pregnancy, and contraception. Results: Vaginal candidiasis was significantly associated with pre-natal consultations (12.2%; p=0.005), university education (17.6%; p=0.002), and a history of sexually transmitted infections (16.3%). There was no statistically significant difference in the contraceptive methods used according to age and marital status. The highest local frequency of 15.8% was observed in Samrbagh and the diagnostic center of Shokat Khanam was found to be with the highest frequency of 15.8% also. All relationships were statistically significant, that is, the study shows trends of infection prevalence as a result of knowledge, lifestyle, and healthcare access. The discovery highlights the risk demographics for these children and underlines the importance of the promotion of preventive health education and screening programs.